Ichnology, Sedimentology and Paleontology of Eocene Calcareous Paleosols from a Palustrine Sequence, Argentina - Melchor, Ricardo Nestor (2002)
Integrated analysis of the ichnology, sedimentology, geochemistry, and fossil content of three trace fossil-bearing calcareous paleosols from the early Eocene Gran Salitral Formation is used to reconstruct the detailed paleoenvironmentaland paleoecological setting of this insect-dominated ichnofossil association. This continental sequence, located in southwestern La Pampa province (Argentina), is composed of palustrine marls and minor lacustrine mudstonesand sandstones arranged in shallowing-upward cycles. The ichnologic association is the first comprehensively described froma palustrine sequence and could be used for future comparisons with other similar assemblages. The ichnofaunais dominated by bee cells, Celliforma germanica, C. roselli, and Rosellichnus isp.; Teisseirei barattinia, an insect trace fossil that is redescribed and recorded for the first time outside its type locality; Taenidium barretti; andSkolithos linearis. The ichnologic association also includes ovoid structures, ornamented burrow fillings, and plant trace fossils (rootlets, rhizoliths, and a tree / shrub stump). Abundant freshwater (Pomacea sp.) and terrestrial gastropods (Plagiodontes spp., Bostryx sp., and Bulimulus sp.) are used to characterize the paleoenvironmental setting. The weakly developed paleosols are interpreted as Inceptisols, developed in a low-gradient lake margin periodicallyexposed to pedogenesis with low (probably saline) vegetation and sparse shrubs. They developed under a semi-arid and warm climate (mean annual temperature higher than 208C). Short saline / alkaline conditions were prevalent during lake lowstands, accompanied by incipient karst development. The association of trace fossils is attributed provisionally to the Coprinisphaera ichnofacies, although its distinctive features and recurrence in time and space may deserve recognition as a separate ichnofacies.